THE EFFECT OF ESG AND EARNINGS MANAGEMENT ON DIVIDEND POLICY OF LISTED FIRM IN INDONESIA - Aulia Nataprawira; Maria Ulpah (Sean Institute, 2023)
This research aims to assess whether there’s a relationship between the concept of Environmental, Social and Governance (ESG) as a replacement indicator for CSR and earnings management towards’ company’s dividend policy as a counter variable of good corporate governance practices. Besides that, this research also aims to assess the relationship between company’s size, return on equity, liquidity ratio, sales growth, risk of a firm and cash flow from operations towards’ company’s dividend policy as a control variable by implementing GLS method as the main method for processing the data & using EVIEWS as the main platform of data processing. Result shows that ESG has a significantly positive relationship towards the Dividend Policy and Earnings Management has significantly negative relationship towards Dividend Policy, indicating that Investor already consider ESG as a main influence on investing in a firm in Indonesia.